(untitled) (Transport systems and technologies, 2021)
The Department of Railwayand Road Transport, lift and care system of Volodymyr Dahl East Ukrainian National University, an energy-saving cooling system for diesel locomotives using phase transitions of the coolant has been developed. The proposed cooling system allows to maintain constant optimal temperatures of cooling objects at ambient temperatures ± 40 ºC and in any mode of operation of the diesel engine. For thermal calculation of the radiator section operating in the mode of the steam condenser, the mathematical model of process of heat transfer from steam to walls of a flat tube at condensation is developed that considers geometrical features of section of a tube. The adequacy of this mathematical model is verified by comparing the simulation results with the obtained experimental data. During the tests, the outlet water temperature, inlet and outlet air temperature, and air pressure in front of and behind the radiator were measured. Having the values of wall temperature, steam temperature and condensate, knowing the value of steam consumption and the experimental heat transfer coefficient, it becomes possible to verify the adequacy of the mathematical model by comparing the simulation results with the obtained experimental data. Schemes of bench equipment, test methods, experimental planning and basic calculation dependences required for testing serial radiator sections of a locomotive in the standard mode of operation and in the mode of steam condensers are presented.